The impact of curriculum quality and brand image on private school competitiveness - Ayuni, Kurata; Margono, Hery; Amir, Ja'far (International Journal of Applied Finance and Business Studies, 2025)
This study investigates the impact of curriculum quality and brand image on school competitiveness, focusing on private schools. Utilizing a quantitative approach, data were collected from 139 respondents, specifically guardians of students enrolled in private school. The analysis was conducted by SEM-PLS approach and using Smart PLS version 4 Application. The findings reveal that curriculum quality significantly affects school competitiveness. Brand image was found to significantly influence school competitiveness, with a moderating effect on the relationship between curriculum quality and competitiveness. These results underscore the necessity for private schools to enhance both their curriculum and brand image to improve their competitive standing in the educational landscape. It is also recommended that the influence of online schools in the digital era, and the views of Gen Z as parents, are also researched.